2003
DOI: 10.1080/00365520310000627a
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Cytoprotective Effect of Protease-activated Receptor-1 in Gastric Epithelial Cells

Abstract: Thrombin is a serine protease involved in many physiological functions and its receptor. the protease-activated receptor-1 (PAR-1), has a wide tissue distribution. We hypothesized that PAR-1 is expressed in gastric epithelial cells and that thrombin can modulate defence mechanisms through PAR-1. The rat gastric epithelial cell line (RMG1) and gastric biopsy specimens from gastritis patients were used in the study. Reverse transcriptase polymerase chain reaction analysis showed that the thrombin receptors PAR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Toyoda et al have reported that PAR 1 protects the gastric mucosa because the secretion of gastric mucin and PGE 2 is promoted by administration of a PAR 1 -activating peptide (31). In addition, Kawabata et al have reported that PAR 2 has a role in both aggressive and protective responses for the gastric mucosa (32,33).…”
Section: Trypsin/ Par Pathway In Reflux Esophagitismentioning
confidence: 99%
“…Toyoda et al have reported that PAR 1 protects the gastric mucosa because the secretion of gastric mucin and PGE 2 is promoted by administration of a PAR 1 -activating peptide (31). In addition, Kawabata et al have reported that PAR 2 has a role in both aggressive and protective responses for the gastric mucosa (32,33).…”
Section: Trypsin/ Par Pathway In Reflux Esophagitismentioning
confidence: 99%
“…Activation of PAR-1 appears to be cytoprotective in a gastric epithelial cell line (Toyoda et al 2003) and in a rat model (Kawabata et al 2004). In both studies, the protective effect was dependent upon cyclooxygenase activity.…”
Section: Effect Of Pars On Epithelial Functionmentioning
confidence: 85%
“…The bulk of evidence points toward expression of PAR-1 and PAR-2, although PAR-3 and PAR-4 may also be present (Toyoda et al 2003, Mule et al 2004. In all regions of the gastrointestinal tract, PARs are expressed on epithelia and thus are in a position to respond to luminal or mucosal serine proteinases.…”
Section: Distribution Of Pars In Gastrointestinal Tractmentioning
confidence: 99%
“…Although we failed to visualize expression of immunoreactive PAR1 in the mucosal epithelial cells of rat and human gastric tissues (Kawabata et al, 2004c), functional PAR1 was detectable in the rat normal gastric mucosal epithelial RGM1 cell line (Sekiguchi et al, 2005;Toyoda et al, 2003) and in the human gastric carcinoma MKN-1 cell line (Miyata et al, 2000). Interestingly, PAR1 stimulation caused delayed (after cosal injury, might stimulate 'unknown cells' that are most probably muscularis mucosa cells expressing both PAR1 and COX-1, as described above, and subsequently cause formation of PGs, leading to suppression of acid secretion by parietal cells in the gastric mucosa ( Fig.…”
Section: Par1-triggered Pge 2 Formation and The Underlying Cell Signamentioning
confidence: 97%
“…Interestingly, some of gastrointestinal functions of PAR1 or PAR2 are attributable to endogenous PGs, although activation of capsaicin-sensitive sensory neurons is also one of the important mechanisms for PAR2-triggered gastrointestinal events including gastric mucosal protection (Kawabata, 2002;Kawabata et al, 2001a;Sekiguchi et al, 2004). Of note is that stimulation of PAR1 or PAR2 actually causes formation of PGs in certain gastrointestinal tissues/ cells (Kong et al, 1997;Kubo et al;Sekiguchi et al, 2005;Toyoda et al, 2003). …”
Section: General Functions Of the Par Receptor Family In The Gastroinmentioning
confidence: 99%